Perception and Understanding of Character Value Based on Local Wisdom in National Heroes Child Literature Reading in Elementary School Teacher in Makassar City - Hasriani, Hasriani; Sofyan, Ryan Rayhana (PT ARRUS Intelektual Indonesia, 2023)
This study aims to describe, explore, and explain: (1) Perception and understanding of the value of character education based on local wisdom in reading children's literature on national heroes, (2) Perception and understanding of the content of character education based on local wisdom in reading literature national hero children, and (3) Perception and understanding of the function of local wisdom-based character education values ​​in reading national hero children's literature. The type of research used is survey research using a qualitative descriptive approach. The research subjects in this study were elementary school teachers in Makassar City. The results showed that the values ​​of character education based on local wisdom were religious, honest, tolerant, disciplined, hard working, creative, independent, democratic, curiosity, national spirit, love of the motherland, appreciating achievement, communicative/friendly, peace-loving, fond of reading, environmental care, social care, and responsibility. The contents of the values ​​of character education based on local wisdom are the values ​​of character education for God Almighty, the values ​​of character education for oneself, the values ​​of character education for fellow human beings, and the values ​​of character education for society/groups/communities. And the functions of character education values ​​based on local wisdom are religious functions, cultural functions, educational functions, and social functions.